1999
DOI: 10.1007/bf02364929
|View full text |Cite
|
Sign up to set email alerts
|

TheR-function method in boundary-value problems with geometric and physical symmetry

Abstract: The traditional mathematical models of fields of various physical nature are boundary-value problems for partial differential equations. The usual statement of a boundary-value problem has the following form:where ffZ is the region in which the solution u is being sought; OfZi, i = 1, 2 ..... m, is a covering of the boundary t?~ of the region f) (the parts c~f~ i are not necessarily different and may be equal to Of)); f and (Pi are known functions (perturbing the field), vector-valued functions, tensors, or po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 3 publications
(7 reference statements)
0
11
0
Order By: Relevance
“…Such relation can be described using the Rfunctions [10]. The R-function method was developed as an improvement of Ritz methods for solving boundary-value problems.…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…Such relation can be described using the Rfunctions [10]. The R-function method was developed as an improvement of Ritz methods for solving boundary-value problems.…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…The simplest function µ satisfying this requirement is the 45 • saw-tooth pattern, but smooth approximations may be constructed using Fourier series, or by methods described by Rvachev (1974). Rvachev, Sheiko and Shapiro (1999) observed that more complex coordinate transformation functions µ i may be constructed as semi-analytic compositions of the above primitive coordinate transformations and Rfunctions. Such coordinate transformations may prescribe periodic, symmetric, and random properties that explicitly depend on the values of the coordinates x i and additional external parameters.…”
Section: Symmetric and Periodic Coordinate Transformationsmentioning
confidence: 99%
“…The papers [4][5][6] propose new approaches that make it possible to apply R-functions to set up normalized equations of complex GOs with symmetry, to be used both in solving boundary-value problems for partial derivative equations modeling various physical fields (it is natural that if geometrical information appears in solution structures, w ( , , )…”
Section: Problem Statementmentioning
confidence: 99%